A Technique to Fabricate La2O2CN2:Tb3+ Nanofibers and Nanoribbons with the Same Morphologies as the Precursors. Issue 3 (22nd December 2014) - Guo, Xiaomin; Yu, Wensheng; Dong, Xiangting; Wang, Jinxian; Ma, Qianli; Liu, Guixia; Yang, Ming
Abstract: Terbium(III)‐doped lanthanum dioxymonocyanamide (La2 O2 CN2 :Tb 3+ ) nanofibers and nanoribbons were fabricated, by the cyanamidation technique, from precursor La2 O3 :Tb 3+ nanofibers and nanoribbons prepared by electrospinning. The morphology of the final products were the same as those of the precursors. X‐ray powder diffraction analysis indicated that the crystal phase of La2 O2 CN2 :Tb 3+ is tetragonal in space group I 4/ mmm . SEM analysis revealed that the thickness and width of the La2 O2 CN2 :Tb 3+ nanoribbons is about 184 nm and 3.53 ± 0.37 μm, respectively, and the diameter of the La2 O2 CN2 :Tb 3+ nanofibers is 175.87 ± 16.23 nm at a 95 % confidence level. When excited with a 274 nm ultraviolet light source, the La2 O2 CN2 :Tb 3+ nanostructures emit predominantly at 543 nm; this emission originates from the 5 D4 → 7 F5 energy level transition of the Tb 3+ ion. It was found that the optimum molar concentration of Tb 3+ ions for doping La2 O2 CN2 :Tb 3+ nanostructures is 3 %. The La2 O2 CN2 :Tb 3+ nanofibers exhibit a higher photoluminescence (PL) intensity than that exhibited by nanoribbons for the same doping concentration. Commission International de l'Eclairage (CIE) analysis demonstrated that color‐tuned luminescence can be obtained by changing the concentration of the doping activator ions and the nanostructure morphology. Possible formation mechanisms for the La2 O2 CN2 :Tb 3+ nanofibers and nanoribbons are also proposed. More importantly, the new technique employed in this paper and the preparation method are of universal significance for providing other rare earth oxycyanamide nanostructures with various morphologies. Abstract : Tb 3+ ‐doped La2 O2 CN2 nanofibers and nanoribbons were fabricated by cyanamidation from precursor La2 O3 :Tb 3+ nanofibers and nanoribbons made by electrospinning. The morphologies of the final products were the same as those of their respective precursors. The La2 O2 CN2 :Tb 3+ nanostructures are tetragonal in structure with space group I 4/ mmm and exhibit excellent luminescence performance.